Macrozoobenthic biodiversity: an indicator of water quality in Ngrowo River, Tulungagung, East Java - Punjungsari, Tyas Nyonita; Azizah, Luthfi Ainul (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
.